The Quivira Historical Society of Alma, Wabaunsee County, Kansas 1901-1912 - Porter, Anthony (Kansas State University, The Chapman Center for Rural Studies, 2016)
This exploration of the amateur history and archaeological organization, the Quivira Society, was a semester-long KSU intern project involving a museum collection of rich primary sources, Indian artifacts, and publications. Although accessioned, the Quivira Collection had never been inventoried nor explored in-depth. This project provides an understanding of the society founders, goals, and accomplishments during the short time it was active. A full inventory of the Quivira Collection is available at the Wabaunsee County Historical Society, Alma, Kansas.
Anthony Porter, “The Quivira Historical Society of Alma, Wabaunsee County, Kansas 1901-1912,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/239.
Keywords: Wabaunsee County; Amateur History; Quivira; Quivira Historical Society; Coronado; Judge John T. Keagy